ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS POWER POINT TERHADAP GURU DI SDN 066656 MEDAN SELAYANG - Polintan Rehulina Sembiring; Paska Sriulina Tarigan; Marina Suri Br Parapat; Dilla Emaninta Tarigan (JURNAL CURERE, 2023)
AbstractThe rapid pace of technology is currently having an extraordinary impact on the world of education, both positive and negative, this depends on how educators and those who are educated use the technology. Effective teachers are certainly able to master subject matter and strategies as well as skills in using various kinds of good teaching media, one of which is using technology, but at this time there are still teachers who only use textbooks as the only learning media. In today's modern and all-technological era, listeners are required to be dynamic towards the rapidly developing technological developments. If the teaching system used by teachers is still conventional, it is feared that students will find it difficult to develop and keep abreast of technological developments in society. By utilizing this media technology, it is very easy for a teacher to convey his knowledge. Not only that, the use of technological media is also very useful for students to capture and understand lessons easily, power point learning media is one of them. This PowerPoint media is an alternative problem solving by developing Microsoft PowerPoint as a learning medium. The purpose of this research is to find out the description: Use of Power Point Based Learning Media for Teachers at SDN 066656 Medan Selayang. The population in this study were all teachers at SDN 066656 Medan Selayang, both civil servants and non-PNS, totaling 12 people. From the results of this study it can be concluded that the use of power point-based learning media for teachers at SDN 066656 Medan Selayang has very good criteria. The better the use of learning media, the better the teacher's performance. Keywords: Learning Media, Power Point Based